The reception of antiquity in Bohemian book culture from the beginning of printing until 1547 - Boldan, Kamil (2014)
This volume presents the historical development and important personalities of the time of transition from manuscript book culture to book printing in the years 1450-1550. The first part of the volume contains a thorough description of historical, social and technical background influencing the development of book printing in Bohemia and Moravia and the impact of book printing production on the contemporary Czech society. The authors described the specific historical conditions in the Kingdom of Bohemia after the pre-reformation Hussite movement. The newly emerged Utraquist confession spread in important parts of Bohemia which led to decrease of social and economic contacts between the Kingdom of Bohemia and Catholic states in Europe. Apart from that the decreased activity of Prague University had negative impact on literacy in Bohemia. These two main reasons were detrimental to the development of book printing in Bohemia. The low quality of first prints was not attractive for educated readers who rather chose better equipped foreign books, mainly in Latin. Book printing in Bohemia soon became a matter of closed Czech speaking public. One of the important consequences of this process was weak reception of humanism and classical antiquity in Czech culture, although the former was partly embraced in Bohemia in previous centuries anyway. The second part of the book presents the first printers and editors of printed books before 1550 with a summary of their publishing activities.